An early career perspective on encouraging collaborative and interdisciplinary research in ecology. Issue 10 (16th October 2019) - Pannell, J. L.; Dencer‐Brown, A. M.; Greening, S. S.; Hume, E. A.; Jarvis, R. M.; Mathieu, C.; Mugford, J.; Runghen, R.
Abstract: There is a growing need for collaborative and interdisciplinary research in addressing global ecological challenges, and early career researchers (ECRs) often play a vital role in such ventures. But despite the desire for such approaches, forming new and interdisciplinary collaborations is risky, and disproportionately so for ECRs, whose perspectives on this topic are rarely heard. Here, we present common perceptions among ECRs regarding opportunities for intra‐ and interdisciplinary collaboration, and barriers preventing such collaboration from taking place. We also discuss possible solutions, and the ecological outcomes of fostering more collaboration. The perceptions discussed have been distilled from a two‐day workshop in New Zealand, aiming to investigate the potential for collaboration between 34 ECRs in distinct ecological disciplines across ten research institutes. Commonality in methodology or research aims was vital for potential collaborations to be considered worthwhile, but differences in spatial or temporal scales were a key disconnect that hindered numerous potential crossovers. Individual connectivity and institutional structures were commonly perceived as barriers to acting collaboratively in general. Specifically, barriers included having a small peer network, lack of access to funding, and concerns over the risk/reward ratio of forming new collaborations. Overcoming barriers will require active, practical support from institutions, funding bodies and mentors, and participants commonly called for specific funding support and the creation of ECR‐focused spaces to better foster collaborative behavior. Fostering interdisciplinary ECR collaborations in ecology was perceived to be useful in creating larger and more useful datasets and tools, and more scalable and transferable models and outcomes. Adopting practices that facilitate more ECR‐led interdisciplinary collaboration will help generate a more integrative understanding of ecological systems globally.